Sharing Scheme of Electronic Medical Records for Air-conditioning Products Based on Blockchain Technology - Xu Chang; Chen Huanxin; Li Zhengfei; Han Linzhi; Zhu Bo; Gong Qijian (Zhileng xuebao)
With the rapid development of big data and intelligence, data have played a decisive role in studies on air conditioning, and possession of good data management models appears to be extremely important. This article proposes, for the first time, a sharing scheme of electronic medical records for air-conditioning products using blockchain as the underlying technology, aiming to build a decentralized system that third-party trust can be omitted in an air-conditioning medical record information sharing platform. Through the use of hashing computing, asymmetric encryption, and a complete network consensus and other technologies, the air-conditioning fault record data of the entire network trustworthiness were achieved, breaking the trust barriers between individuals and enterprises. Research shows that the platform of electronic medical records for air-conditioning products based on blockchain technology can endow the data stored in it with the characteristics of immutability, relative transparency, and traceability to ensure complete credibility of the platform data. At the same time, its storage cost is relatively low, with an average storage cost of only 2 kB per case, which presents significant application prospects.